Using kisspeptin to assess GnRH function in an unusual case of primary amenorrhoea - Vimalesvaran, S (Endocrinol Diabetes Metab Case Rep, 2017)
SUMMARY: Primary amenorrhoea is defined as the failure to commence menstruation by the age of 15 years, in the presence of normal secondary sexual development. The potential causes of primary amenorrhoea extend from structural to chromosomal abnormalities. Polycystic ovarian syndrome (PCOS) is a common cause of secondary amenorrhoea but an uncommon cause of primary amenorrhoea. An early and prompt diagnosis of PCOS is important, as up to 30% of these women are predisposed to glucose intolerance and obesity, with the subgroup of women presenting with primary amenorrhoea and PCOS displaying a higher incidence of metabolic dysfunction. We describe a case of an 18-year-old female presenting with primary amenorrhoea of unknown aetiology. Although initial investigations did not demonstrate clinical or biochemical hyperandrogenism or any radiological evidence of polycystic ovaries, a raised luteinising hormone (LH) suggested a diagnosis of PCOS. If PCOS was the correct diagnosis, then one would expect intact hypothalamic GnRH and pituitary gonadotropin release. We used the novel hormone kisspeptin to confirm intact hypothalamic GnRH release and a GnRH stimulation test to confirm intact pituitary gonadotroph function. This case highlights that kisspeptin is a potential unique tool to test GnRH function in patients presenting with reproductive disorders. LEARNING POINTS: Polycystic ovarian syndrome (PCOS) can present with primary amenorrhoea, and therefore, should be considered in the differential diagnosis. PCOS is a heterogeneous condition that may present in lean women with few or absent signs of hyperandrogenism. GnRH stimulation tests are useful in evaluating pituitary function; however, to date, we do not have a viable test of GnRH function. Kisspeptin has the potential to form a novel diagnostic tool for assessing hypothalamic GnRH function by monitoring gonadotropin response as a surrogate marker of GnRH release. Confirmation of intact GnRH function helps consolidate a diagnosis in primary amenorrhoea and gives an indication of future fertility.